Some Problems in Nonclassical Algebraic Geometry - Plotkin, B. (Український математичний журнал, 2002)
We describe the general approach to a nonstandard geometry with the emphasis on associative algebras. Описано загальний підхід до нестандартної алгебраїчної геометрії з акцептом на асоціативних алгебрах.